If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -7n + -3 = -2 Reorder the terms: 1 + -3 + -7n = -2 Combine like terms: 1 + -3 = -2 -2 + -7n = -2 Add '2' to each side of the equation. -2 + 2 + -7n = -2 + 2 Combine like terms: -2 + 2 = 0 0 + -7n = -2 + 2 -7n = -2 + 2 Combine like terms: -2 + 2 = 0 -7n = 0 Solving -7n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '-7'. n = 0 Simplifying n = 0
| 5x+y=-23 | | 6w+2w+3=9 | | -6+4(n-4)=5(2n+4) | | 7p+3-5p=-11 | | 3x-4x+1=1 | | 3x-9x+2=26 | | 3f+5=f | | 5p+2p=-4 | | 3x+8+6=50 | | 3v=75 | | -9x-4=68 | | v+3+7v=11 | | v+v=-4 | | x^2-66x+64=0 | | 6r+4r=16+2r | | 9p=2r-4f | | 2(2x-5)=2 | | 3t+3t=-9+9t | | x+1+1=6 | | 12=7+c | | -2(x-1)=-3x | | 6s+4=20+5s | | 9x^2-8x^3= | | 3(y+7)=2y-5 | | -6p+7p=0 | | 14+2y=3 | | -36-8x=7x+24 | | 6x+3x=18 | | 7+3x+5=-15 | | 2x^2-14x+2=0 | | 14-(4m+5)=4+3m-16 | | 5(3+z)-(8z+9)=-4z |